2022
DOI: 10.1002/oby.23588
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a grocery shopping intervention designed to improve diet adherence in diabetes: a randomized trial

Abstract: Objective The goal of this study was to examine the potential of an optimal‐defaults intervention to promote grocery purchases corresponding to a diet for diabetes. Methods In total, 65 adults diagnosed with or at increased risk for type 2 diabetes who grocery shopped at one of two study stores were randomized to one of three groups: Defaults, Online, or Control. All groups received diabetes‐friendly recipes. In addition, the Online group was asked to grocery shop online during a 3‐week intervention, and the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…In the primary outcomes paper for the overarching study, the research team reported that average dollars spent at study grocery stores did not differ between group ( 21 ) . However, multiple participants perceived online shopping to be more expensive than shopping in-person ( n 10 out of the 43 that responded to the open-ended question about online grocery shopping), and a few indicated the inability to use coupons as a barrier ( n 7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the primary outcomes paper for the overarching study, the research team reported that average dollars spent at study grocery stores did not differ between group ( 21 ) . However, multiple participants perceived online shopping to be more expensive than shopping in-person ( n 10 out of the 43 that responded to the open-ended question about online grocery shopping), and a few indicated the inability to use coupons as a barrier ( n 7).…”
Section: Resultsmentioning
confidence: 99%
“…Findings from this study suggest that it was feasible to implement an optimal defaults intervention to improve the nutritional quality of grocery purchases for people with or at-risk for diabetes ( 21 ) and collect all study data remotely. Most participants found the methods, data collection and prefilled default grocery carts to be acceptable and useful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous interventions designed to change grocery shopping habits have primarily focused on providing education and produced only modest changes in food purchasing, with minimal evidence of long-term maintenance of change in dietary quality. [17][18][19] These suboptimal results are unsurprising given the difficulty of selfregulation in the modern food environment. 17,20,21 There are several tools for behavior change that can enhance selfregulation and motivation, that, when added to a foundation of nutrition education, might improve grocery shopping purchases, and ultimately, short and long-term adherence to dietary guidelines.…”
Section: Achieving Stimulus Control Through Grocery Shopping Behaviormentioning
confidence: 99%